Positive fractional variable order discrete-time systems*. Issue 1 (July 2017) - Malesza, Wiktor
Abstract: This paper introduces and characterizes linear Positive Fractional Variable Order Discrete-Time Systems described in pseudo state-space form for different types of fractional variable order differences. The verifiable necessary and sufficient conditions of positivity are also given.